Renal dysfunction in liver disease. (October 2019) - Michael, Emma; Nadarajah, Luxme; Blunden, Mark; Alazawi, William
Abstract: Acute kidney injury is a frequently encountered complication in patients with decompensated liver disease. As in the general population, pre-renal, renal and post-renal causes should be excluded, although particular consideration must be given to sepsis and bleeding. Hepatorenal syndrome (HRS) is a type of acute kidney injury found in patients with advanced liver disease, the diagnosis of which should be made only after excluding other causes. Acute and chronic renal dysfunction in cirrhosis is common, and both confer a negative impact on morbidity and mortality. As such, it is essential for all clinicians involved in the care of these patients to be able to identify them in both inpatient and outpatient settings, so that appropriate management strategies can be implemented. This article reviews the aetiology and management of renal dysfunction in patients with chronic liver disease. HRS has a high morbidity and mortality, and its pathogenesis, diagnosis and specific management are highlighted here.